Police and Politics in India : Colonial Concepts, Democratic Compulsions: Indian Police 1947-2002 - Dhillon, Kirpal (Brill | Manohar Publishers & Distributors, 2024)
Essentially a sequel to the author's earlier work, Defenders of the Establishment: Ruler-supportive Police Forces of South Asia , a history of the Indian police from ancient times to 1947, this book deals with police history, covering some 55 years since Indian independence. Writing about contemporary institutions and events is a risky proposition and more so in this country as the very nature of its polity is forever in a state of flux, not always for the better. Law enforcement and politics are essential, irrevocable and interdependent features of state power and are prone to feed on each other for sustenance. However, unwarranted political manipulation of state institutions, especially the police and the magistracy, a marked feature of Indian law enforcement mechanisms in recent times, is bound to impair democratic freedoms and human rights of the people. Also, all social and political institutions are the product of a nation's historical and philosophical experience through the ages. Indian police is no exception. In some ways, this is like saying that every society gets the police it deserves. Does it follow, therefore, that the Indian people are doomed to live for ever with a callous, overbearing, communalized, often corrupt and unaccountable police force? Not really. Only if the Indian state were to set in motion a calibrated process of substantial reforms in the outdated system of law enforcement, rooted in the mid-nineteerth century, most forms of distortions in police functioning would vanish.